Establishment of an experimental system to study the influence of electrical field on cochlear structures. (10th July 2015) - Reich, Uta; Warnecke, Athanasia; Szczepek, Agnieszka J.; Mazurek, Birgit; Olze, Heidi
Highlights: New experimental model of the effects of electrical field on cochlear tissues is presented. Electrical field can induce the loss of auditory hair cells. Electrical field can induce neuronal degeneration. Abstract: Treatment of partial hearing loss with the combined electrical and acoustical stimulation (EAS) aims at restoring the hearing while preserving the residual hearing. The aim of present study was to establish an in vitro system to study the effects of an electrical field on the auditory hair cells and spiral ganglion cells. Cochlear tissues containing the organ of Corti, spiral limbus and spiral ganglion neurons were dissected from post-natal Wistar rats (p3–p5) and cultured in the micro-channels. Electric current was homogenously applied on the apical, medial and basal parts of explants. Biphasic rectangular pulses were applied continuously over a period of 30 h or 42 h and the explants were fixed and stained to visualize the hair cells and neurites. Application of electrical field for 30 h has not induced significant changes in the number of inner or outer hair cells when compared to the control. However, after 42 h of electric stimulation, the number of hair cells decreased significantly by about 30 %. The medial and basal fragments were particularly affected. The number of neurites has not been influenced but significant neuritic beading, consistent with neurodegeneration, was observed after 42 h of electric stimulation. Although performed with immature auditory tissues, our findings hint at the possibility of particular electric current inducing damage or loss of auditory hair cells, which should be considered when designing EAS electrodes.